Rice Husk Silica Liquid Protects Pancreatic β Cells from Streptozotocin-Induced Oxidative Damage - Hsin-Yuan Chen; Yi-Fen Chiang; Kai-Lee Wang; Tsui-Chin Huang; Mohamed Ali; Tzong-Ming Shieh; Hsin-Yi Chang; Yong-Han Hong; Shih-Min Hsia (MDPI AG, 2021)
Type 2 diabetes mellitus is a complex multifactorial disease characterized by insulin resistance and dysfunction of pancreatic β-cells. Rice husk silica liquid (RHSL) is derived from rice husks and has not been explored in diabetes mellitus until now. Previous studies showed that rice husk is enriched with silica, and its silica nanoparticles are higher more biocompatible. To investigate the potential protective role of RHSL on pancreatic β cells, we utilized RIN-m5F pancreatic β cells and explored RHSL effect after streptozotocin (STZ)-stimulation. The recovery effects of RHSL were evaluated using flow cytometry, Western blotting, and immunofluorescence analysis. Results of our study showed that RHSL reversed the cell viability, insulin secretion, reactive oxygen species (ROS) production, and the change of mitochondria membrane potential (ΔΨm) in STZ-treated RIN-m5F cells. Moreover, the expression of phospho-receptor-interacting protein 3 (p-RIP3) and cleaved-poly (ADP-ribose) polymerase (PARP), phospho-mammalian target of rapamycin (p-mTOR), and sequestosome-1 (p62/SQSTM1) were significantly decreased, while the transition of light chain (LC)3-I to LC3-II was markedly increased after RHSL treatment in STZ-induced RIN-m5F cells. Interestingly, using autophagy inhibitors such as 3-methyladenine (3-MA) and chloroquine (CQ) both showed an increase in cleaved-PARP protein level, indicating apoptosis induction. Taken together, this study demonstrated that RHSL induced autophagy and alleviated STZ-induced ROS-mediated apoptosis in RIN-m5F cells.